Suppressing the Level of Corruption in Kampar District: A Study of The Impact of Accountability, Audit Opinions, Publication of Financial Statements, Audit Results And Follow-Up Of Audit Results - Djamil, Nasrullah; Anggraini, Maiza (InJEBA : International Journal of Economics, Business and Accounting, 2023)
This study aims to evaluate the effects of accountability, audit opinion, financial statement disclosure, audit findings, and follow-up on audit results in reducing corruption levels within the Regional Apparatus Organization (OPD) of Kampar Regency. Conducted through a survey method, the study utilized a purposive sample of 50 accounting and finance professionals to achieve its objectives. Consistent with the research objectives, this study adheres to a conventional academic structure, utilizing clear and objective language, precise technical terminology, and a logical progression of ideas presented in a balanced manner. Primary data was collected via questionnaire distribution. Multiple linear regression tests were utilized to analyze the data. Results indicate that accountability, audit opinion, financial statement disclosure, audit findings, and follow-up of audit results significantly suppress the level of corruption in the Kampar district. It is imperative to follow up on audits to maintain transparency and accountability in the district. Based on simultaneous testing, the evidence suggests that factors such as accountability, audit opinion, disclosure of financial statements, audit findings, and follow-up on audit results play a role in reducing the incidence of corruption in Kampar district, in 2023.